Photocatalytic regeneration of reactive cofactors with inP quantum dots for the continuous chemical synthesis - Chakraborty, Indra Narayan; Jain, Vanshika; Roy, Pradyut; Kumar, Pawan; Vinod, Chathakudath P.; Pillai, Pramod P. (ACS Catalysis, 2024)
The shuttling of redox-active nicotinamide cofactors between the light and dark cycles is the key to the continuous production of biomass in photosynthesis. The replication of such processes in artificial photosynthetic systems demands fast photoregeneration as well as simultaneous integration of these nicotinamide cofactors into the dark cycle. Here, we report the design of an artificial photosynthetic system for the continuous production of butanol via the constant photoregeneration and consumption of nicotinamide cofactors, powered by an indium phosphide quantum dot (InP QD) photocatalyst and alcohol dehydrogenase (ADH) enzyme, respectively. A strong electrostatic attraction between the oppositely charged InP QDs and electron mediators significantly enhanced the charge extraction and utilization processes, enabling a fast (similar to 30 min, with a turn over frequency of similar to 1333 h(-1)), quantitative (>99%), and selective photoregeneration of enzymatically active nicotinamide cofactors in the light cycle. These photoregenerated nicotinamide cofactors were further coupled in the dark cycle to trigger the ADH oxidoreductase enzyme for the production of butanol, via sequential as well as simultaneous light-dark cycles. The amount of butanol produced under simultaneous light-dark cycles was higher than the stoichiometric limit, proving the constant regeneration and consumption of nicotinamide cofactors in light and dark cycles, respectively. Thus, a proper design and integration of the InP QD-based photocatalytic cycle with the enzymatic cycle led to the effective electron shuttling between light and dark cycles, as seen in photosynthesis.
Keywords: artificial photosynthesis; biologicalcofactors; charge transfer; indiumphosphide; Photocatalysis; quantum dots